1987
DOI: 10.1016/0035-9203(87)90397-x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from meningococcal disease during an epidemic in The Gambia, West Africa

Abstract: Mortality from meningococcal disease was determined during an epidemic in a rural area of The Gambia with few medical resources, but where a system of registration of births and deaths had been established before the introduction of a primary health care programme. 33 deaths were recorded among 127 patients, a case mortality rate of 26%. 84% of deaths occurred within the first 24 h of illness and many patients died before they could reach any source of treatment. Previous studies, based on regional statistics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

1988
1988
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 4 publications
0
13
0
2
Order By: Relevance
“…Among 132 children Յ14 years of age in Gondar from 1990 to 1994, the CFR for bacterial meningitis was 28%, while the N. meningitidis-specific CFR was 16% (15). CFRs for epidemic meningococcal disease in the meningitis belt range from 3 to 30% (6,17,26). They are probably underestimated due to the fact that septicemic patients might die before reaching the health facility (17,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 132 children Յ14 years of age in Gondar from 1990 to 1994, the CFR for bacterial meningitis was 28%, while the N. meningitidis-specific CFR was 16% (15). CFRs for epidemic meningococcal disease in the meningitis belt range from 3 to 30% (6,17,26). They are probably underestimated due to the fact that septicemic patients might die before reaching the health facility (17,25).…”
Section: Discussionmentioning
confidence: 99%
“…CFRs for epidemic meningococcal disease in the meningitis belt range from 3 to 30% (6,17,26). They are probably underestimated due to the fact that septicemic patients might die before reaching the health facility (17,25). The low N. meningitidis-specific CFR observed in our study (4.2%), with few of the patients confirmed with meningococcal disease presenting with ecchymoses or petechiae (Table 2), is most likely due to our inclusion criteria, which focused on the clinical signs of meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…11,[15][16][17][18]25 In both of our treatment groups, the CFR was lower than those reported from epidemiological surveillance or prospective studies undertaken during meningitis epidemics. [26][27][28][29] This difference might be due to the exclusion of individuals with the most severe disease and the study conditions that ensured full-time availability of medical staff and material. Previous studies have shown similar CFR and recovery rates without sequelae at 72 h to those in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Infection by Veisseria meningitidis can result in serious invasive disease (meningitis, meningococcaemia, Waterhouse-Friderichsen syndrome) with high case-fatality rates and frequent sequelae [1][2][3]. In Europe, most cases of meningococcal invasive diseases occur sporadically and are caused by serogroup B, while outbreaks or epidemics are caused mainly by serogroup C or A.…”
Section: Introductionmentioning
confidence: 99%